Lymphoma of the Uvula: Clinical, Morphological, Histopathological, and Genetic Characterization. A Nationwide Danish Study From 1980 to 2019 - Iversen, Lars; Eriksen, Patrick Rene Gerhard; Andreasen, Simon; Clasen-Linde, Erik; Homøe, Preben; Wessel, Irene; von Buchwald, Christian; Heegaard, Steffen (Frontiers in Surgery, 2021)
Background: In the head and neck region the uvula is a rare site for extranodal lymphomas to develop. In this national study, we present six cases and provide an overview of the current literature, characterizing the clinical and histopathological features of lymphomas involving this location. Materials and Methods: Clinical information was obtained retrospectively from patient records in a nationwide Danish study covering from 1980 through 2019. In order to validate the diagnoses, uvular tissue specimens were examined histologically and immunohistochemically and if relevant for subtyping, cytogenetic rearrangements were investigated. Results: We present six cases of lymphomas involving the uvula, of which four of the cases were diagnosed with a B-cell lymphoma (two diffuse large B-cell lymphomas, one extranodal marginal zone B-cell lymphoma and one Mantle cell lymphoma), while two were diagnosed with a T-cell lymphoma (one peripheral T-cell lymphoma and one natural killer/T-cell lymphoma). Presenting symptoms included swelling, pain and ulceration of the uvula. Treatment was comprised of radiotherapy and/or chemotherapy, with T-cell lymphomas showing a poorer outcome than B-cell lymphomas. Conclusion: Lymphoma of the uvula is rare, with few case reports being reported in the literature. The most frequent histological subtypes reported are extranodal marginal zone B-cell lymphoma and peripheral T-cell lymphoma. When encountering a swollen, painful and/or ulcerated uvula, the clinician should always consider malignancy as a possible cause. Lymphoma of the uvula is a possible diagnosis and if this is the case, there is a high risk of disseminated disease at the time of diagnosis.